PEMANFAATAN TEKNIK CODING DUAL TONE MULTIPLE FREQUENCY (DTMF) DAN TELEPON SELULER PADA MODEL SISTEM PINTU ELEKTRONIK DI JURUSAN TEKNOLOGI INFORMASI POLITEKNIK NEGERI SAMARINDA - Ahmad Rofiq Hakim; Agus Triyono (Politeknik Negeri Samarinda, 2016)
The study entitled Use of Dual Tone Multiple Frequency (DTMF) and Cell Phones on System Model Door Electronics at the Department of Information Technology Samarinda State Polytechnic aims to build Model Systems Doors Electronic using Dual Tone Multiple Frequency (DTMF) and Cell Phones to be applied in the Department of Information Technology Samarinda State Polytechnic. This research was conducted through the stages of prototype development and the process of communication between devices using DTMF (Duat Tone Multiple Frequency) is a matrix of rows and columns using the frequency. The end result of this research is a model of Electronic Door Systems in the Department of Information Technology Samarinda State Polytechnic aims to build Electronic Door Systems Model using Dual Tone Multiple Frequency (DTMF) and Cell Phones Kata Kunci : Electronic locks, DTMF, Cell Phones